폐암의 정위적 체부 방사선치료 시 체적 설정과 호흡주기에 따른 선량평가 - 이득희(Deuk Hee Lee); 박은태(Eun Tae Park); 김정훈(Jung Hoon Kim); 강세식(Se Seik Kang) (방사선기술과학, 2016)
Stereotactic body radiotherapy is effective technic in radiotherapy for low stage lung cancer. But lung cancer is affected by respiratory so accurately concentrate high dose to the target is very difficult. In this study, evaluated the target volume according to how to take the image. And evaluated the dose by photoluminescence glass dosimeter according to how to contour the volume and respiratory range. As a result, evaluated the 4D CT volume was 10.4 cm3 which was closest value of real size target. And in dose case is internal target volume dose was 10.82, 16.88, 21.90 Gy when prescribed dose was 10, 15, 20 Gy and it was the highest dose. Respiratory gated radiotherapy dose was more higher than internal target volume. But it made little difference by respiratory range. Therefore, when moving cancer treatment, acquiring image by 4D CT, contouring internal target volume and respiratory gated radiotherapy technic would be the best way. 저병기 폐암은 정위적 체부 방사선치료 방식이 높은 효과를 나타내지만, 호흡에 의한 움직임으로 인해 정확한 선량의 조사가 쉽지 않다. 이에 본 연구는 움직이는 표적을 대상으로 영상획득 방식에 따른 체적을 분석하고, 체적 설정방식 및 호흡주기에 따른 선량을 유리선량계를 이용하여 평가하였다. 그 결과, 체적 획득의 경우 4D CT가 $10.4cm^3$로 실제 체적인 $12.3cm^3$에 가장 근접한 결과를 나타냈다. 선량평가에서는 ITV가 처방선량 10, 15, 20 Gy에서 각각 10.82, 16.88, 21.90 Gy로 가장 높은 값을 보였으며, RGRT가 좀 더 높은 값을 나타내었으나 호흡주기에 따른 결과는 유의한 차이를 나타내지 않았다. 따라서 움직이는 종양의 치료 시 4D CT를 이용하여 영상을 획득 후 ITV를 설정하여 RGRT방식으로 치료하는 것이 유리할 것으로 사료된다.